2009
DOI: 10.1021/mp9000662
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Interactions with Model Lipid Membranes: Applications in Drug Discovery and Drug Delivery

Abstract: The transport of drugs or drug delivery systems across the cell membrane is a complex biological process, often difficult to understand because of its dynamic nature. In this regard, model lipid membranes, which mimic many aspects of cell-membrane lipids, have been very useful in helping investigators to discern the roles of lipids in cellular interactions. One can use drug-lipid interactions to predict pharmacokinetic properties of drugs, such as their transport, biodistribution, accumulation, and hence effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
353
0
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(368 citation statements)
references
References 90 publications
1
353
0
14
Order By: Relevance
“…Firstly, silver nanoparticles are important antimicrobial agents. [48][49][50][51][52] AgNPs are able to destroy bacterial cell walls, to trigger conformational changes of the ion channel, to cause changes of channel opening and dysfunctions. Therefore understanding silver nanoparticle -membrane interactions is essential to understand their toxic effects on both human health and the environment.…”
Section: Silver Nanoparticle -Membrane Interactionmentioning
confidence: 99%
“…Firstly, silver nanoparticles are important antimicrobial agents. [48][49][50][51][52] AgNPs are able to destroy bacterial cell walls, to trigger conformational changes of the ion channel, to cause changes of channel opening and dysfunctions. Therefore understanding silver nanoparticle -membrane interactions is essential to understand their toxic effects on both human health and the environment.…”
Section: Silver Nanoparticle -Membrane Interactionmentioning
confidence: 99%
“…The interaction between cell membranes and nanocarriers, such as dendrimers, is very important, because in the most cases carriers have to get across the lipid bilayer without disrupting it. Previous studies based on atomic force microscopy (AFM) [12][13][14][15][16][17] isothermal titration calorimetry (ITC), fluorescence correlated spectroscopy (FCS) [17][18], in vitro experiments [13,[19][20] and molecular dynamics simulations (MD) [14,17,[21][22][23][24] showed that cationic dendrimers disrupt lipid bilayers by forming holes on the bilayer surface and may remove lipids from it. The degree of the disruption depends on the size and charge of the dendrimer.…”
Section: Introductionmentioning
confidence: 99%
“…Liposomes are widely used as model systems of biological membranes, since both contain lipid bilayers as their basic structural unit [12]. This way, investigating the effect of foreign molecules on the structure and thermal behavior of liposomes, we can obtain basic information on the physicochemical level of toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that the interaction with the CM of target bacteria is an essential step in the antimicrobial action of AMPs [13][14][15][16][17] and interactions of this type have been investigated using a variety of model membranes [18][19][20][21][22][23] . These model membranes are usually formed from lipid mixtures with a head-group composition that reflects the molar ratio of the major lipids in the bacterial membrane, namely PE, phosphatidylglycerol (PG), Lys-PG and cardiolipin (CL).…”
mentioning
confidence: 99%